In vivo protein corona patterns of lipid nanoparticles. Issue 2 (4th January 2017) - Amici, A.; Caracciolo, G.; Digiacomo, L.; Gambini, V.; Marchini, C.; Tilio, M.; Capriotti, A. L.; Colapicchioni, V.; Matassa, R.; Familiari, G.; Palchetti, S.; Pozzi, D.; et al.
Abstract : In vitro and in vivo biological identity of nanoparticles are substantially different. Abstract : In physiological environments ( e.g. the blood), nanoparticles (NPs) are surrounded by a layer of biomolecules referred to as a 'protein corona' (PC). The most tightly NP-bound proteins form the so-called hard corona (HC), the key bio-entity that determines the NP's biological identity and physiological response. To date, NP-HC has been almost exclusively characterized in vitro, while NP–protein interactions under realistic in vivo conditions remain largely unexplored. In this study, we thoroughly characterized the in vivo HC of a NP formulation that forms around lipid nanoparticles with a lipid composition equal to that of clinically used liposomal amphotericin B (AmBisome®) after the recovery of the NPs from the blood circulation of FVB/N mice 10 minutes post intravenous administration. In vitro HC formed by 10 minutes incubation of NPs in FVB/N mouse plasma was used for comparison. Here we show that the biological identity ( i.e. size, zeta-potential and aggregation state) of NPs in vivo is significantly different from that acquired in vitro . Furthermore, the variety of protein species in the in vivo HC was considerably larger. The present work has demonstrated that characterization of the in vivo HC is essential to provide an accurate molecular description of the biological identity of NPs in physiological environments.